Diagnóstico de incidências de manifestações patológicas com a utilização da metodologia matriz gut - estudo de caso - Lima, Maria Gilcelannia Holanda (Universidade Federal Rural do Semi-Árido, 2019)
The fall of the financial market in Civil Construction area during recent years and the increase in inputs and labor influenced the pursuit for constructions with low cost and faster execution, in addition to hiring disqualified labor. Such factors contribute to the early onset of pathological manifestations - studied by the field of pathology - adversely contributing to the building's lifespan, durability and development. Given the problem in question, it became interesting to conduct a study with 7 apartments in a three storey residential, located in Mossoró-RN. The pathological manifestations present specific characteristics that help the identification of its nature, source and mechanisms involved. A noteworthy factor is that every building, however well planned, is subject to the incidence of pathological manifestations. The diagnosis was made by visual inspection (with the aid of a camera), digital caliper (for the determination of crack openings) and also the non destructive ultrasound test of the concrete (for determining the concrete quality of the building pillars). After this survey of pathological manifestations the matrix tool Gravity, Urgency and Tendency (GUT) was applied to determine the degree of prioritization for the solution of pathological manifestations.With the results obtained it was possible to conclude that the most urgent incidents to be treated are related to crack openings of the building pillars that compromise the structure in regards to both aesthetic and security aspects. Another worrisome manifestation is the infiltration caused by a leak in the water tank, causing the appearance of other pathological manifestations.
Monografia
Keywords: Construção Civil; Grau de Priorização; Manutenção; Vida Útil; Civil construction; Degree of prioritization; Maintenance; Lifespan; ENGENHARIAS::ENGENHARIA CIVIL